Potential increase in coastal wetland vulnerability to sea-level rise suggested by considering hydrodynamic attenuation effects - Rodriguez, Jose F. (2017)
Fil: School of Enginering and Centre for Water Security and Environmental Sustainability, The University of Newcastle, Callaghan 2308, Australia